Karyotypic characterization by mitosis, meiosis and C-banding of Eriopis connexa Mulsant (Coccinellidae: Coleoptera: Polyphaga), a predator of insect pests - Maffei, Eliane Mariza Dortas; Gasparino, Eliane; Pompolo, Silvia das Gracas (Hereditas, 2000)
Eriopis connexa presents a chromosome number of 2n = 18 + XX for most females analyzed and a meioformula of n = 9 + Xyp for all males. A small metacentric B chromosome restricted to females occurred in 10% of our sample and, when submitted to C-banding, it was shown to be almost completely euchromatic. Chromosome pairs 2 and 3 had satellites and probably contained the nucleolar organizer regions (NORs). C-band analysis also revealed that the constitutive heterochromatin was localized in the centromeres of all chromosomes in the complement.
Keywords: Karyotypic characterization; Eriopis connexa; Insect Pests